A terceirização da guarda e da gestão de documentos na Prefeitura de Belo Horizonte e suas implicações na gestão, difusão e acesso - Suellen Alves de Melo (2024)
This thesis analyzed the outsourcing of records custody and management in the direct and indirect administrations of the City of Belo Horizonte during the period between 1997 and 2021. To do so, in addition to gathering the administrative contracts made during the specified period, it also verified whether the organs and entities that used records outsourcing services had eliminated or transferred records to Public Archive of the City of Belo Horizonte in order to discuss the implications of outsourcing for records management, archival diffusion, and qualified access. As for methodology, the research qualified as exploratory. Utilizing both quantitative and qualitative methods, the documentary research involved the collection and analysis of records gathered through the Official Gazette of the Municipality of Belo Horizonte, requests for access to information, and records accumulated by the Records Management Coordination of the Public Archive of the City of Belo Horizonte. A total of 57 contracts regarding records custody and records management were identified, with 42 of them established with the aim of outsourcing the custody of public records. The research data also indicate that the organs and entities of the City Hall carry out eliminations and transfers; however, the frequency of eliminations is lower than the frequency of transfers, especially concerning entities of the indirect administration. The initial overall values of the outsourcing contracts for records custody and records management were higher than the amounts allocated to the Public Archive of the City of Belo Horizonte between 2009 and 2021. It was noted the necessity for the aforementioned institution to receive the necessary financial and human resources for its operation, particularly concerning the implementation of records management programs, as well as for the Public Archive of the City of Belo Horizonte to be placed in a prominent position within the administrative structure of the City Hall. It is concluded that the outsourcing of custody and records management has not been advantageous for the municipal administration and society. However, if outsourcing occurs, the Public Archive of the City of Belo Horizonte should be consulted during the planning, contracting, and management of records custody and records management services. Contracts related to such services should not include records that are not classified and evaluated, and the retention periods and final destinations established in the retention schedule of the City Hall should be taken into account during the time the records are under outsourced custody.